Association Between Sense of Coherence and Frailty: A Cross-Sectional Study in China - Chen, Hao; Fu, Hua; Ye, Bo; Wang, Yi; Yan, Huihui; Chen, Yingwei; Xu, Jixiang; Nie, Xin; Gao, Junling (Frontiers in Psychiatry, 2022)
Purpose: Frailty is an emerging global public health burden. Most existing studies have focused on risk factors for frailty, focusing less on protective factors against frailty. This study aimed to examine the association between the sense of coherence (SOC), the most common construct of salutogenesis and frailty status among community residents. Method: A cross-sectional study was conducted among 7970 community residents aged ≥ 65 years in three cities in China from June 2019 to October 2020. Frailty was operationalised as the sum of self-reported fatigue, resistance, ambulation, illness and loss of weight (FRAIL scale). The 2 test was used to analyse the distribution difference of frailty in demographic, behavioural and SOC levels. Confounder-adjusted multinomial logistic regression was used to examine the association between SOC and frailty. Results: The prevalence of pre-frailty and frailty was 43.1% and 8.0%, respectively. The results of the confounder-adjusted regression showed that older adults with moderate-level SOC (odds ratio, OR: 0.61, 95% CI: 0.54–0.69) and strong-level SOC (OR: 0.55, 0.48–0.64) had lower odds of being pre-frail compared to those with weak SOC. It also showed that older adults with moderate-level SOC (OR: 0.32, 95% CI: 0.27–0.40) and strong-level SOC (OR: 0.22, 95% CI: 0.16–0.29) had lower odds of being frail compared to those with weak SOC. Conclusion: SOC may be a protective factor against to frailty. Improving SOC may be a strategy to prevent frailty among Chinese community-dwelling elders.